One‐year persistence of potentially inappropriate medication use in older adults: A population‐based study. Issue 6 (3rd February 2020) - Roux, Barbara; Sirois, Caroline; Simard, Marc; Gagnon, Marie‐Eve; Laroche, Marie‐Laure
Abstract : Aims: To assess the 1‐year persistence of potentially inappropriate medication (PIM) use and identify associated factors in community‐dwelling older adults in Quebec, Canada. Methods: A population‐based cohort study was conducted using the Quebec Integrated Chronic Disease Surveillance System. Individuals insured by the public drug plan and aged ≥66 years who initiated a PIM between 1 April 2014 and 31 March 2015 were followed‐up for 1 year. PIMs were identified using the 2015 Beers criteria. One‐year persistence of PIM use was defined as continuous treatment with any PIM, without interruption for more than 60 days between prescriptions refills. Poisson regression models were performed to identify factors associated with 1‐year persistence of any PIM. Results: In total, 25.1% of PIM initiators were persistent at 1 year. In non‐persistent individuals, the median time to PIM discontinuation was 31 days (interquartile range 21‐92). Individuals were more persistent at 1 year with antipsychotics (43.9%), long‐duration sulphonylureas (40.2%), antiarrhythmics/immediate‐release nifedipine (36.5%) and proton pump inhibitors (36.0%). Factors significantly associated with persistence were an increased age, being a man and having a high number of medications and chronic diseases, especially dementia, diabetes and cardiovascular diseases. Conclusions: One‐quarter of community‐dwelling older adults are continuously exposed to PIMs. To optimize medication prescribing in the older population, further interventions are needed to limit the use of PIMs most likely to be continued, especially in individuals most at risk of being persistent and also particularly vulnerable to adverse events.